Meta-Analysis of Integrated Primary and Behavioral Health Care Interventions for Treating Substance Use Among Adults - Balkin, Richard S. (Journal of addictions & offender counseling, 2019)
This meta-analysis detected low effects in reducing substance use (Hedges's g = -0.11) in favor of using integrated primary and behavioral health care (IPBH) compared with treatment-as-usual approaches for adult patients with substance use. The impact of IPBH was limited.